PENGARUH LOKASI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MINUMAN READY TO DRINK (RTD) KEDAI THREE THAI TEA DESA AWUNIO KECAMATAN KOLONO KABUPATEN KONAWE SELATAN - Manan, La ode Abdul; Titop, Herman; Yuliasari, Windi (Sultra Journal of Economic and Business, 2022)
This study aims to determine the Influence of Location and Promotion on the Decision to Purchase Ready To Drink Bottled Tea Drinks (RTD) Kedai Three Thai Tea Awunio Village Kolono District Kolono District South Konawe Regency.To achieve this goal, qualitative and quantitative data, data collection techniques with observation, interviews, and custody. The population in the study was a three thai tea shop customer. The sample in this study used analysis with multivariate (correlation or multiple regression), then the number of sample members was at least 10 times the variable studied (independent + dependent). In this study there are 2 independent variables and 1 dependent variable (there are 3 variables), then 15 x 10 = 75. So the number of samples in this study is as many as 75 respondents. . The data is collected through questionnaires and analyzed using multiple linear regression analysis and using hypothesis tests, i.e. partial t tests and simultaneous F tests. The results of the analysis showed that there was a significant and positive influence between location and promotion on purchasing decisions, both partially and simultaneously.